2012
DOI: 10.1080/10640266.2012.689212
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Selves of Adult Women With Anorexia Nervosa

Abstract: Adopting the construct of possible selves, which are conceptions of our selves in future situations, the objective of this study was to investigate how anorexia patients differ from a non-clinical control group in their conceptions of the future on qualitative content, and the four quantitative dimensions positive and negative emotional valence, and beliefs about probability and controllability. The Possible Selves Statements Test was employed. Participants presented 14 possible selves by completing the questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Our participants' preoccupation with time may be a feature of AN with a longer history, and this requires further study. A negative view of the future, expressed by some of our participants, has been noted (Erikson, Hansson, & Lundblad, ; Sternheim et al, ), and a wish for the relief of social isolation was found in letters requesting inpatient care at an Eating Disorders Unit (Gorse, Nordon, Rouillon, Pham‐Scottez, & Revah‐Levy, ). The harshness with which our participants judged themselves and restricted any potentially pleasurable activity is consistent with previous studies (Sternheim et al, ; Tierney & Fox, ).…”
Section: Discussionmentioning
confidence: 66%
“…Our participants' preoccupation with time may be a feature of AN with a longer history, and this requires further study. A negative view of the future, expressed by some of our participants, has been noted (Erikson, Hansson, & Lundblad, ; Sternheim et al, ), and a wish for the relief of social isolation was found in letters requesting inpatient care at an Eating Disorders Unit (Gorse, Nordon, Rouillon, Pham‐Scottez, & Revah‐Levy, ). The harshness with which our participants judged themselves and restricted any potentially pleasurable activity is consistent with previous studies (Sternheim et al, ; Tierney & Fox, ).…”
Section: Discussionmentioning
confidence: 66%
“…However, it remains unclear how egocentric and allocentric spatial processing are related to the individual's perception of the self and others, and this will be the focus of the current study, which will adopt a multidimensional approach and draw upon personal construct theory (PCT) (Kelly, 1955). From this theoretical perspective, EDs are viewed as "strategies" for dealing with the developmental issues characterizing interpersonal relationships and the formation of identity (Button, 1993;Erikson et al, 2012). Kelly (1955) considered individuals as scientists involved in the anticipation of their worlds through the formulation and testing out of hypotheses, or constructions of events, and revision of these if they are invalidated (Winter and Button, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the experience of possible selves have been observed in individuals with eating pathology as compared to healthy control participants. For example, the possible selves described by participants with AN have been found to be more negative than those reported by healthy control participants (Erikson, Hansson, & Lundblad, 2012). Another study by the same research group demonstrated that women with EDs rate 'desirable' possible selves more negatively as compared to healthy control participants (Erikson, Hansson, & Lundblad, 2014).…”
Section: Fear Of Self In Eds: Empirical Supportmentioning
confidence: 99%
“…These studies support the role of vulnerable self-identity in EDs in that they suggest a link between difficulties in identity formation and these disorders. Identity disturbance coupled with unconditional negative representations of the self (Cooper, 1997;Erikson, Hansson, & Lundblad, 2012;Waller et al, 2003;Waller, Ohanian, Meyer, & Osman, 2000), may reflect susceptibility for investment in a feared self.…”
Section: Fear Of Self In Eating Disorders 16mentioning
confidence: 99%